Hubungan Social Support dengan Teacher Efficacy dimediasi oleh Work Engagement - Tenaya Nur Kaulika Tammy; Dinda Dwarawati (UNISBA Press, 2024)
Abstract. Teacher efficacy is one factor that has the potential to differentiate between teachers, because there are differences in perceptions regarding efficacy when teaching to different students or in various situations. Social support is an important factor in teacher efficacy. Work Engagement can play a role in the relationship between social support and teacher efficacy. However, cultural differences can affect all three. Apart from that, social support can come from various sources outside of family, friends and those closest to you. This research aims to determine the relationship between social support and teacher efficacy through work engagement in 214 special education school teachers in Bandung City. The method used in this research is a quantitative method with Spearman Rank & Structural Equation Modeling (SEM) correlation test analysis. The measuring instrument used is the Revised-Multidimensional Scale of Perceived Social Support (R-MSPSS) measuring instrument developed by Ho and Chan and adapted by Oktarina et al (2021), Teacher's Sense of Efficacy Scale adapted by Maulana et al (2020) and The Utrecth Work Engagement Scale which has been adapted by Febrian Kristiana et al (2018). The research results show that there is a positive relationship between social support and teacher efficacy in special school teachers in Bandung City (r = 0.338). Then work engagement does not have a mediating role. Abstrak. Teacher efficacy merupakan salah satu faktor yang berpotensi membedakan antar guru, karena terdapatnya perbedaan persepsi terkait efficacy ketika mengajar pada siswa yang berbeda atau dalam berbagai situasi. Social support merupakan faktor penting dalam teacher efficacy. Work Engagement dapat berperan dalam hubungan social support dan teacher efficacy. Namun, perbedaan budaya dapat mempengaruhi ketiganya. Selain itu, social support dapat muncul dari berbagai sumber di luar keluarga, teman, dan orang terdekat. Penelitian ini bertujuan untuk mengetahui hubungan social support terhadap teacher efficacy melalui work engagement pada 214 orang guru SLB di Kota Bandung. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif dengan analisis uji korelasi Spearman Rank & Structural Equation Modelling (SEM). Alat ukur yang digunakan adalah alat ukur Revised-Multidimensional Scale of Perceived Social Support (R-MSPSS) yang dikembangkan oleh Ho dan Chan dan diadaptasi oleh Oktarina et al (2021), Teacher’s Sense of Efficacy Scale diadaptasi oleh Maulana et al (2020) dan The Utrecth Work Engagement Scale yang telah diadaptasi oleh Febrian Kristiana et al (2018). Hasil penelitian menunjukan bahwa hubungan positif antara social support dan teacher efficacy pada guru SLB di Kota Bandung (r = 0,338). Lalu work engagement tidak memiliki peran sebagai mediasi.